2021
DOI: 10.3390/brainsci11091155
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Subjective Memory Impairment, Depressive Symptoms, Sleep, and Physical Activity in African American and Asian American Elderly

Abstract: Background: Subjective memory impairment (SMI) is associated with negative health outcomes including mild cognitive impairment and Alzheimer’s disease. However, ethnic differences in SMI and disparities in risk factors associated with SMI among minority populations are understudied. The study examined the ethnic differences in SMI, whether SMI was associated with depressive symptoms, sleep, and physical activity (PA), and whether the associations vary across racial/ethnic groups. Methods: Participants included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Finally, the current sample was not statistically powered to effectively examine the influence of race across multiple individual racial identity groups. Given that differences in subjective cognitive ratings were observed across various racial identity groups in the current study and have been reported elsewhere (Ganbat & Wu, 2021;Jang et al, 2022;Lee et al, 2021), future work should look to aggregate datasets in order to fully examine the effect of race on SCD ratings within former contact sport athletes, particular in relation to other SCD-associated factors.…”
Section: Limitationsmentioning
confidence: 62%
“…Finally, the current sample was not statistically powered to effectively examine the influence of race across multiple individual racial identity groups. Given that differences in subjective cognitive ratings were observed across various racial identity groups in the current study and have been reported elsewhere (Ganbat & Wu, 2021;Jang et al, 2022;Lee et al, 2021), future work should look to aggregate datasets in order to fully examine the effect of race on SCD ratings within former contact sport athletes, particular in relation to other SCD-associated factors.…”
Section: Limitationsmentioning
confidence: 62%
“…In stark contrast, the International group is much more diverse and includes individuals from 69 countries who identified over 60 different native languages. Therefore, though we found no convincing group differences between our very broad International group and the Anglosphere group in terms of reported SCD and iADL difficulties, such differences may exist in smaller ethnic or racialized groups as demonstrated in other studies (Ganbat & Wu, 2021;Lee et al, 2021). Given the heterogeneity in our sample, such detailed analyses are not feasible and are beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 54%
“…Findings are mixed with respect to difficulties with iADLs (Hackett et al, 2020; Tappen et al, 2010), and SCD (Borelli et al, 2022; Casillas et al, 2019; Garcia et al, 2021; Jackson et al, 2017; Jang et al, 2022; Nakhla et al, 2021; Pluim et al, 2023; Spitzer & Weber, 2019; Tolea et al, 2020; Wu, 2016). This variability in findings may be related to the use of various assessment approaches, disparities in study recruitment or access to care, and group differences in characteristics other than culture that may also contribute to SCD such as education, socioeconomic status, and depression (Borelli et al, 2022; Jang et al, 2022; Lee et al, 2021; Rodriguez et al, 2021; Spitzer & Weber, 2019). Therefore, it is difficult to ascertain whether culture or these social and health factors best explain differences in self-reported cognitive changes because these factors are often confounded.…”
mentioning
confidence: 99%
“…Moreover, certain populations may underreport or interpret symptoms differently due to cultural norms, beliefs, and attitudes toward mental health and illness. 20,21 In addition, it is worth noting that the brief mental status evaluation employed in this study lacks sensitivity in detecting subtle cognitive impairment. To address this limitation, the utilization of a more sensitive tool like the Montreal Cognitive Assessment would have been preferable.…”
Section: Discussionmentioning
confidence: 99%